THE EFFECT OF INNOVATION AND CREATIVITY ON CONSUMER SATISFACTION IN FISHING AND RESTAURANT SMEs H. ROMLI IN PABUARAN SUBANG - Zahro Asyifa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The purpose of this research is to identify and clarify the ways in which innovation and creativity at the fishing UMKM and the H.Romli Restaurant contribute to patrons' overall happiness. Explanatory study using a quantitative methodology is used. Sample data were calculated using Non Probability sampling technique with purposive sampling method, and the number of respondents as many as 100 was obtained from the calculation of the Lameslow formula; the population of this study consisted of regular buyers or consumers at fishing UMKM and H.Romli's Restaurant. Multiple linear regression is used in the data collection questionnaire. Research shows that the innovation variable affects customer satisfaction, and the creativity variable affects customer satisfaction, as shown by the t test findings of 4.380 and 4.573, respectively. The F-value of 67.689 indicates that originality and creativity have an effect on client happiness. While other factors account for the remaining 41.7% of the equation, innovation and creativity account for 58.3%. It follows that customers will be content with a company's offerings if those offerings are the result of thoughtful innovation and originality.Keywords: Innovation, Creativity, Consumer Satisfaction